Characteristics of brain activation in high-level football players at different stages of decision-making tasks off the ball: an fMRI study - Huang, Ming-Hao; Lang, Jian; Li, Ju; Qin, Zhe; Cao, Ya-Ping (Frontiers in Human Neuroscience, 2023)
Objective: This study aimed to examine the neural mechanisms underlying the decision-making process of off-ball movements among high-level football players and ordinary college students, as well as the effect of long-term skill training on these neural mechanisms using functional magnetic resonance imaging (fMRI). Methods: A total of 40 participants, divided into the expert group (EG) consisting of 20 high-level football players and novice group (NG) consisting of ordinary college students, were included in the experiment. The participants performed the motor video observation and button-decision-making tasks, and fMRI data were acquired, pre-processed, and analysed. Results: Whole-brain fMRI scans of the EG and NG when they made decisions about running without the ball revealed significant differences in brain activity between the groups during motor video observation and button-decision-making tasks. According to the behavioural data, the EG made more correct decisions than the NG; however, there was no significant difference in reaction speed (p <0.05). As a result of video observation, the front parietal cognitive area, primary somatosensory cortex, visual cortex, and insula were simultaneously activated in the EG and NG; however, there was no significant difference between the two groups regarding activated brain regions (false discovery rate (FDR) corrected to p <0.05). The cuneus and inferior temporal gyrus brain regions, which are responsible for attention, visual perception, and memory, were activated in the EG. In the case of button-press decisions, the left superior temporal gyrus, left inferior temporal gyrus, and left middle occipital gyrus were more activated in the NG than in the EG (FDR corrected to p <0.05). Conclusion: This study demonstrated that during motor video observation, the EG's sports experience and professional knowledge can help them achieve better visual information processing strategies in specific areas of sports. During button decision-making, the EG was more economical, whereas the NG required more brain function activity to process visual information, confirming the "neural efficiency" hypothesis.